Fracture studies on carbon steel straight pipes having off-centred circumferential through-wall crack under finite compliance. (May 2020) - Saravanan, M.; Vishnuvardhan, S.; Gandhi, P.; Raghava, G.; Khan, I.A.; Bhasin, V.; Chattopadhyay, J.
Abstract: The level-3 Leak-Before-Break (LBB) assessment of nuclear piping system is based on simplified fracture mechanics calculations. A postulated through-wall circumferential crack is shown to be stable even under extreme loading conditions. An important aspect of this fracture assessment, which is generally not considered, is the reduction in load at the cracked section that occurs due to the local and global compliance of the piping system. In this study, the effect of piping system compliance, crack size and crack location on the load carrying capacity of SA-333 Gr. 6 carbon steel pipes was analysed. Experimental investigations were performed on 8 ״ NB Schedule 100 pipes (Outer diameter 219 mm and wall thickness of approx. 12.6 mm) under quasi-static four point bending loads. Out of the six fracture tests, one specimen had a through-wall circumferential crack at the centre (along the length of pipe) and the remaining five tests had off-centred cracks. While the initial crack size showed a weak influence on the load carrying capacity of a stiff piping system, the effect of crack location was, however, quite significant. Calculations based on twice-elastic slope (TES) method and limit analysis of uncracked piping system (in some cases) for evaluation of load carrying capacity of pipes under finite compliance may lead to large safety margins. Graphical abstract: Image 1 Highlights: Fracture studies on straight pipes having off-centred crack under finite compliance. Maximum measured load compared with the collapse load obtained using TES criterion. Initial crack size had a weak influence on load carrying capacity of stiff piping system. Location of crack had a substantial influence on the load-displacement response.